Telecom Compatible Quantum Key Distribution - Learning from Classical Coherent Communication - Marquardt, Christoph (2019 Optical Fiber Communications Conference and Exhibition, OFC 2019 - Proceedings, 2019)
Quantum key distribution (QKD) enables secure cryptography that is safe against future attacks by quantum computers. We show recent advances in continuous variable QKD and highlight similarities and differences to classical coherent communication.
CRIS-Team Scopus Importer:2019-05-21